Brain delivery of proteins via their fatty acid and block copolymer modifications - Yi, Xiang (2013)
It is well known that hydrophobic small molecules penetrate cell membranes better than hydrophilic molecules. Amphiphilic molecules that dissolve both in lipid and aqueous phases are best suited for membrane transport. Transport of biomacromolecules across physiological barriers, e.g. the blood-brain barrier, is greatly complicated by the unique structure and function of such barriers. Two decades ago we adopted a simple philosophy that to increase protein delivery to the brain one needs to modify this protein with hydrophobic moieties. With this general idea we began modifying proteins (antibodies, enzymes, hormones, etc.) with either hydrophobic fatty acid residues or amphiphilic block copolymer moieties, such as poy(ethylene oxide)-poly(propylene oxide)-poly(ethylene oxide) (pluronics or poloxamers) and more recently, poly(2-oxasolines). This simple approach has resulted in impressive successes in CNS drug delivery. We present a retrospective overview of these works initiated in the Soviet Union in 1980s, and then continued in the United States and other countries. Notably some of the early findings were later corroborated by brain pharmacokinetic data. Industrial development of several drug candidates employing these strategies has followed. Overall modification by hydrophobic fatty acids residues or amphiphilic block copolymers represents a promising and relatively safe strategy to deliver proteins to the brain.